INDIKASI DAN KETERAMPILAN RESUSITASI JANTUNG PARU (RJP) - Kaliammah Ganthikumar (DiscoverSys Inc., 2016)
Cardiopulmonary resuscitation (CPR) is a livesaving technique which is very useful in many emergencies, such as heart attack or near drowning, in which someone’s breathing or heartbeat has stopped.The American Heart Association recommends that everyone - doesn’t have experience or medical personnel can start CPR with chest compression. Chest compression can help to save someone’s life eventhough you doesn’t have knowledge. Its better then doing nothing. CPR can delivery enough oxygen to brain and vital organ till definitive medication is given to restore normal heart rthym. The supply of oxygen to brain is distupted for eight to te minutes can cause death.CPR for a cardiac arrest I starting from circulation then breathing then airway( C-B-A)